KEKONGRUENAN DAN KESEBANGUNAN PADA PERANGKAT UPACARA ADAT KEBO-KEBOAN ALASMALANG - Cahyani, Ika Arum; Setiawan, Toto Bara; Yudianto, Erfan (Kadikma, 2018)
Abstract. Ethnomatematics is a habit and customs in a community group and there is a mathematical concept without being realized by the community. This research was conducted in Alasmalang village, especially Krajan Singojuruh Banyuwangi hamlet. The purpose of this study is to describe the ethnomatematics of Alasmalang kebo-keboan traditional ceremony which will then be developed into a worksheet for students. This student worksheet is equipped with a collection of questions that enhance creativity and teamwork called Escape Sheet. This research includes the type of qualitative research with an ethnographic approach. This research takes the object in the form of traditional ceremonies for kebo-keboan and its speakers, namely the Chair of Customary Institutions and Buldrah. Data collection is done with 3 methods, namely observation, documentation and interviews. The results of data collection were analyzed and presented descriptively. The results of the research that have been presented show the existence of mathematical concepts such as 2d figure,, similarity and congruence. In addition, the results also show the possibility of ethnomatematics that has been found to be developed into a collection of questions in the form of Escape Sheet. Keywords: Ethnomathematics, Kebo-Keboan Traditional Ceremony, Congruency, Similarity